Efficiency of Rice Farms during Boro Period in Bangladesh: An Econometric Approach (Global Journal of Management and Business Research, 2013)
Bangladesh is an agro-based economy. To achieve self sufficiency of food-grain production in Bangladesh, it is very important to increase the production of rice, particularly Boro rice. Production may be increased, firstly, by introducing modern technology in the long-run or secondly, by improving the efficiency of the farmers in the short-term. In this study, researcher is focusing to achieve the target by improving the efficiency of the farmers. Modern econometric tools, like Stochastic Frontier Approach (SFA) is used for measuring the efficiencies of the farmers. Empirical results of this study shows that average technical, allocative and economic efficiency of the farmers during Boro period are 86 per cent, 75 per cent and 64 per cent respectively.